Application of the Dilution Doctrine in Trademark Registration as Legal Protection for Trademarks in Indonesia - Pandam Bayu Seto Aji; Martitah Martitah; Ristina Yudhanti (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This research examines and analyzes the concept and regulation of the trademark dilution doctrine, which has long developed in the United States, as a form of legal comparison, as well as the implementation of the dilution doctrine in the substantive examination of trademark registration in Indonesia. The research method used is normative juridical research employing statutory, conceptual, comparative, and case study approaches. This study uses secondary data in the form of primary, secondary, and tertiary legal materials, which are then qualitatively analyzed. Data collection techniques involve literature study by tracing widely published written information. The results of this study show that trademark violations in Indonesia are dominated by imitation marks, thereby requiring legal reform in trademark law through the adoption of the dilution doctrine similar to that of the United States. Article 21 paragraph (1)(c) of the Indonesian Trademark and Geographical Indication Law mandates the application of the dilution doctrine, although it does not explicitly regulate it. This indicates that Indonesia has the potential to implement the dilution doctrine. However, the significant differences between the United States and Indonesia make full implementation of the doctrine difficult. One of the main challenges in implementing the dilution doctrine is the communal character of Indonesian society. When analyzed using Jeremy Bentham’s Utilitarianism Theory, the result shows that implementing the dilution doctrine would produce greater pain for Indonesia. Therefore, adjustments and legal formulations are needed to accommodate the interests of all parties, including clear and detailed regulations that govern dispute resolution and evidentiary standards in court. The implementation of the dilution doctrine in substantive examination also needs to be tightened to reduce future trademark disputes.